Seeing stars with digital eyes. - Appell, D. (IEEE spectrum)
The event horizon of a black hole and the most distant astronomical object ever observed are two of the many new views of the universe delivered to scientists by charge-coupled devices. This paper discusses the Advanced CCD Imaging Spectrometer and the X-ray CCDs used in the device